"I won't cycle on a route like this; I don't think I fully understood what isolation meant": A critical evaluation of the safety principles in Cycling Level of Service (CLoS) tools from a gender perspective. (October 2018) - Xie, Linjun; Spinney, Justin
Highlights: Provides evidence of gender bias in the design of Cycling Level of Service tools (CLoS). Demonstrates that social safety should be a critical factor in CLoS assessment. Focuses attention on the relationship between CLoS gender bias, social safety and cycle route designation. Highlights the gender performative nature of CLoS and the need for gender mainstreaming in relation to planning tools. Demonstrates use of mobile methods to enhance reliability of findings. Abstract: This paper contributes to debates on gender, mobility and planning through an analysis of Cycling Level of Service tools (CLoS). Whilst many UK cities have had some success increasing overall cycling numbers in recent years, women are still far less likely to cycle, often because of concerns with journey quality related to traffic safety and social safety. CLoS tools are used by planners and engineers to assess existing routes and ensure they are safe, direct and continuous. However, whilst CLoS tools are seen to provide objective measures of some principles, we argue that they fail to attribute enough importance to gendered differences in perceptions of social safety. Based upon qualitative go-along and interview data, we assess the Welsh CLoS tool, demonstrating that it allows routes considered to be unrideable by female cyclists to be designated as rideable because there is no requirement to take mandatory remedial action regarding what are shown to be critically low scores on indicators of social safety. Whilst larger studies are required to validate these findings, our data suggests that the safety component of the CLoS tool can only be considered objective from a male point of view and inadequately considers the perspectives and needs of women. Moreover, we argue that in mandating socially unsafe routes as safe, CLoS actively reproduces gendered 'essences' such as vulnerability. As a result we suggest that CLoS urgently needs to be incorporated into gender and equalities audits if it is to accurately reflect the needs of more diverse user groups.